-9+-2+4f=7f-3

Simple and best practice solution for -9+-2+4f=7f-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9+-2+4f=7f-3 equation:


Simplifying
-9 + -2 + 4f = 7f + -3

Combine like terms: -9 + -2 = -11
-11 + 4f = 7f + -3

Reorder the terms:
-11 + 4f = -3 + 7f

Solving
-11 + 4f = -3 + 7f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-7f' to each side of the equation.
-11 + 4f + -7f = -3 + 7f + -7f

Combine like terms: 4f + -7f = -3f
-11 + -3f = -3 + 7f + -7f

Combine like terms: 7f + -7f = 0
-11 + -3f = -3 + 0
-11 + -3f = -3

Add '11' to each side of the equation.
-11 + 11 + -3f = -3 + 11

Combine like terms: -11 + 11 = 0
0 + -3f = -3 + 11
-3f = -3 + 11

Combine like terms: -3 + 11 = 8
-3f = 8

Divide each side by '-3'.
f = -2.666666667

Simplifying
f = -2.666666667

See similar equations:

| x-1/4-2=x-4/3 | | 2/3c=6 | | a=120p+0.07p | | g(x)=2t^3-t^2+28t+51 | | a=120+0.07p | | -n/-6=20 | | m-(-23.6)=-12.8 | | a^4-15a^2-16=0 | | 4(-9)(-5)(0)(-3)= | | a^4-256=0 | | t-(-3)=34 | | A=P+0.07P | | 3x/7-5=19 | | 4m+7=0 | | -23=e-(-9) | | 6u-9u=6+-2+u | | A=120+0.07 | | 6x+5=-14x | | 9x+(-5x)= | | 0.5(0.7x+3)-0.6(1.6x-0.2)=x | | 15-8b=-4(9b-5) | | 3y^2-16x^2+96x-42y-13=0 | | 2+10x=x-7+-8 | | 5x-4+3=36 | | 45x^3-63x^2+5x-7=0 | | -6(8f-9)=24+5f | | 5*t-18-4*t=-36 | | (r-5)(r+9)=-31 | | x=-0.60x+108 | | t+t+t+27=t+51+72+94 | | y=-0.60x+108 | | y=-0.60+108 |

Equations solver categories